The Influence of Teaching Approaches on Students' Perspectives on Challenges and Opportunities in Learning English at Ban Kaeng Sri Phoom School, Thailand - Andi Azizah Nahdah Atzila; Syahrir; Husnani Aliah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Despite English being a compulsory subject in Thailand, the country's English proficiency remains low. This research explores the relationship between teaching methods and students' perceptions of challenges and opportunities in learning English at Ban Kaeng Sri Phoom School, Thailand. This study aims to understand how teaching methods can be optimized to enhance motivation and effectiveness in learning English in Thailand. By identifying specific challenges faced by students, the research paves the way for developing appropriate solutions. A mixed methods approach was employed, combining quantitative data from questionnaires (administered to students) with qualitative data from classroom observations. The research spanned four months, from July to October 2023. Classroom observations revealed student behaviors that indicated a lack of focus and motivation. Additionally, intellectual diversity among students presented challenges. The questionnaire results provided insights into students' perceptions of learning English, their confidence levels, and the effort they put into their studies. The findings suggest that current teaching methods may not be sufficiently engaging or cater to the diverse needs of students. This highlights the need for teachers to adopt more interactive and individualized approaches. The study also emphasizes the importance of collaboration between teachers, students, and families to create a supportive learning environment.